Problems of single-industry towns: world experience and Russian practice - A. G. Glebova; V. N. Zelensky; A. S. Lazareva (Вестник университета)
The process of industrialisation in Russia was accompanied by the creation of many cities, the economy of which is associated with a certain industry. At the same time, the city is completely dependent on one or more of the same type of enterprises. Such an enterprise is called a city-forming one, since it employs 30 % of all working people in the city, and their families make up half of the urban population. The dependence of the city on the enterprise that is one of the main problems, since the state of the enterprise directly affects the economy of the entire city. The activity of the enterprise determines the unemployment rate in the city, the size of the city budget and the state of engineering networks. In the case of a crisis and the shutdown of the enterprise, the economy of a single-industry city will face huge problems. The purpose of the study was to identify the problems of the Russian single-industry towns, and review foreign methods of leveling them. The object of the study were the Russian single-industry towns defined by the Russian Government Decree No. 1398-r dated on 29.07.2014 (revised on 21.01.2020) “On Approval of the List of Monoprofile Municipal Entities of the Russian Federation (Mono-Cities)”. The main research method was comparative analysis. The main problems of single-industry towns in Russia have been formulated: infrastructure provision and monoprofile economy. A comparative analysis of domestic and foreign experience in solving these problems is carried out and the directions of modernisation of Russian single-industry towns are proposed. Issues of legal support for the implementation of the proposed recommendations require further elaboration.